Copper-Catalyzed Eglinton Oxidative Homocoupling of Terminal Alkynes: A Computational Study - Jesús Jover (Journal of Chemistry)
The copper(II) acetate mediated oxidative homocoupling of terminal alkynes, namely, the Eglinton coupling, has been studied with DFT methods. The mechanism of the whole reaction has been modeled using phenylacetylene as substrate. The obtained results indicate that, in contrast to some classical proposals, the reaction does not involve the formation of free alkynyl radicals and proceeds by the dimerization of copper(II) alkynyl complexes followed by a bimetallic reductive elimination. The calculations demonstrate that the rate limiting-step of the reaction is the alkyne deprotonation and that more acidic substrates provide faster reactions, in agreement with the experimental observations.